(untitled) (Medicine Today, 2026)
Introduction with Objective: The aim of the present study was to evaluate the etiology and short-term outcome of Meningoencephalitis. Materials and Methods: A hospital-based observational study was conducted in the Department of Medicine, Sir Salimullah Medical College Mitford Hospital, from July 22 to June 2023. 50 Patients enrolled within the study period with features of Meningoencephalitis fulfilling the inclusion and exclusion criteria. Ethical clearance for the study was obtained from the Ethical Review Committee. A detailed history, clinical examination was carried out. In addition to the routine blood test, CSF samples were collected as soon as possible from all patients unless contraindicated and sent for cytological, biochemical, and microbiological tests. Data were collected in the pre-formed standard data collection form, recorded in separate case records and analyzed by SPSS 26.0. Results: Our results demonstrate the most of the cases (24, 48%) was tubercular meningoencephalitis, followed by (15, 30%) bacterial meningoencephalitis and (11,22%) viral meningoencephalitis. Gram positive diplococci found in 5 (33%) participants, 1 (6%) participant detected to had S. pneumoniae in PCR in the bacterial meningoencephalitis group. 1 (9%) participant detected to had Herpes simplex and 1 (9%) Varicella zoster in PCR among viral meningoencephalitis group. MTB detected in 8 (33%) participants in the tubercular meningoencephalitis group. Most of the participants 7 (46%), 18 (75%) who was diagnosed with bacterial and tubercular meningoencephalitis were severely disabled respectively, 7 (63%) who was diagnosed with viral meningoencephalitis had good recovery. Mean ± SD of the duration of hospital stay of the tubercular meningoencephalitis was highest (31.91 ± 12.46 days). Most of the participants who had a poor outcome presented with headaches, GCS<8 (OR 9.84),increased ESR, decreased Glucose (mg/dl) in CSF, abnormal CT/MRI Findings, low GOS- E score, increased duration of hospital stay between the participants who had a poor outcome, were statistically significant (p<0.05). Conclusion: In this study tubercular meningoencephalitis was the most common microbiological etiology of meningoencephalitis and most of the patients 18 (75%) were severely disabled, 3 (12.5%) died. Medicine Today 2026, Vol.38 (1): 3-9